Transplantasi Organ Tubuh Perspektif Tafsir Al-Qur’an Tematik Kementerian Agama RI - Tamlikhan, M. (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2024)
Organ transplantation is a new method of treatment in the world of medicine, which has caused many differences of opinion among contemporary scholars. So that the Ministry of Religion of the Republic of Indonesia, formed the Thematic Tafsir al-Qur’an Writing Team of the Ministry of Religion of the Republic of Indonesia as one of the efforts to answer the dynamics and developments that are currently happening in society. This research aims to see and re-explain how organ transplantation is carried out through the perspective of Tafsir Al-Qur’an Thematic of the Ministry of Religion of the Republic of Indonesia, so that they can find out how significant the interpretation of organ transplantation is the answer to contemporary problems. In conducting this study, the author uses a thematic approach method in which the researcher will research certain concepts regarding organ transplantation through the Thematic Tafsir al-Qur’an Writer Team of the Ministry of Religion of the Republic of Indonesia. So in analyzing it, the author uses a descriptive-analytical method, namely by describing the views of contemporary scholars and then analyzing them using existing data. From the results of this study, the author found the conclusion that organ transplantation is the process of transplanting living or dead human organs to other people's damaged limbs. In interpreting the verses about organ transplantation, the Thematic Tafsir Al-Quran Writing Team of the Ministry of Religion of the Republic of Indonesia does not directly explain the interpretation method used, but in its interpretation it is more of a fiqh approach in answering the question of whether or not organ transplantation can be carried out. So that this interpretation has significance as an answer to the demands of the Qur’an shalihun li kulli zaman wa makan which the Qur’an will always be relevant for all times and places.